Androgen induces gonadal soma-derived factor, Gsdf, in XX gonads correlated to sex-reversal but not Dmrt1 directly, in the teleost fish, northern medaka (Oryzias sakaizumii). (15th November 2016) - Horie, Yoshifumi; Myosho, Taijun; Sato, Tadashi; Sakaizumi, Mitsuru; Hamaguchi, Satoshi; Kobayashi, Tohru
Abstract: In the inbred HNI-II strain of Oryzias sakaizumii, Dmy and Gsdf are expressed in XY gonads from Stages 35 and 36, respectively, similarly to the inbred Hd-rR strain of Oryzias latipes . However, Dmrt1 respectively becomes detectable at Stage 36 and 5 days post hatching (dph) in the two strains. In XX HNI-II embryos, 17α-methyltestosterone (MT) induces Gsdf mRNA from Stage 36, accompanied by complete sex-reversal in all treated individuals (MT, 10 ng/mL), while Dmrt1 mRNA was first detectable at 5 dph. In XX d-rR, MT induced Gsdf mRNA expression and sex-reversal in only some of the treated individuals. Together, these results suggest the testis differentiation cascade in XY individuals differs between the HNI-II and Hd-rR strains. In addition, it is suggested that androgen-induced XX sex-reversal proceeds via an androgen- Gsdf - Dmrt1 cascade and that Gsdf plays an important role in sex-reversal in medaka. Highlights: In XY Oryzias sakaizumii, the testis determination pathway differs from Oryzias latipes . Testis determination proceeds in parallel via both Dmy-Gsdf-Dmrt1 and Dmy-Dmrt1 . In XX embryos, MT induces Gsdf, but not Dmrt1 directly. Gsdf plays an important role in androgen-induced XX sex-reversal in medaka.